Moisture Dependent Physical and Thermal Properties of Coleus Tuber - Chandrasekar, V.; Kailappan, R.; Kasthuri, R.; Rajamani, K. (Journal of Agricultural Engineering, 2014)
Some important physical and thermal properties of coleus tubers were determined in the moisture range of 466.62 to 21.52% (d.b). Selected physical properties namely weight, size; bulk density, particle density and porosity increased with increase in moisture content. Thermal properties viz. specific heat and thermal conductivity increased with increase in moisture content while thermal diffusivity recorded a decreasing trend.